Finite element analysis of glass fiber-reinforced polyamide engine oil pan subjected to localized low velocity impact from flying projectiles - Mouti, Zakaria; Westwood, Keith; Long, Darren; Njuguna, James A. K. (Cranfield University, 2012)
This paper investigates low velocity impact involving a glass fiber-reinforced polyamide engine oil pan as part of a complete new development of thermoplastic components. The assessment of the impact resistance has driven the need to employ LS DYNA for finite element modeling in order to benchmark and predict the strength and fracture behavior of stressed plastic parts. In order to develop a reliable predictive capability and to validate simulations, complete components were manufactured by injection molding techniques for the experimental samples. Low velocity impact investigations were carried out using a gas gun and a falling weight tester in order to simulate impact events to which the oil pan is subjected whilst in operational service. This was intended to point out damage tolerance and failure mechanisms likely to occur in the structure. The study results show the significant contribution of the design in terms of shock absorption. Specific oil pan design with protective ribbing combined with a superior material considerably improves the impact resistance. The paper provides results and discussions on experimental and finite element analysis investigations before concluding with some remarks.
Keywords: finite element analysis; low velocity impact; impact resistance; glass fiber reinforced polyamide; thermoplastics; oil pan